Maritime Spatial Planning 2019
DOI: 10.1007/978-3-319-98696-8_11
|View full text |Cite
|
Sign up to set email alerts
|

Taking Account of Land-Sea Interactions in Marine Spatial Planning

Abstract: This chapter reflects on marine/maritime spatial planning (MSP) from a Land-Sea Interaction (LSI) perspective. It raises questions about the role and limitations of MSP in addressing sustainable development of the world’s oceans as many of the issues it is concerned with are inextricably connected to activity on the land. The chapter starts by identifying LSI considerations in some of the key documents that are guiding the establishment of MSP. It then sets out a framework for considering LSI and explores the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 8 publications
0
16
0
4
Order By: Relevance
“…Inclusiveness is composed of such principles as leaving no one behind (7), nondiscrimination (8), participation (9), subsidiarity (10) and intergenerational equity (11). Each principle is described accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…Inclusiveness is composed of such principles as leaving no one behind (7), nondiscrimination (8), participation (9), subsidiarity (10) and intergenerational equity (11). Each principle is described accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…However, the role of MSP in addressing what is called "land-sea interactions" (LSI) has been a topic for much debate and confusion. Indeed, in 2017 MSP practitioners met at a conference to discuss how to address land-sea interactions in MSP (Kidd et al, 2019). The practice of addressing LSI in MSP is, however, still limited and highly debated.…”
Section: Target 141 Marine Pollutionmentioning
confidence: 99%
“…The practice of addressing LSI in MSP is, however, still limited and highly debated. Full integration of terrestrial and marine planning systems has been suggested as a way to facilitate better considerations for LSI, but it bears a number of challenges (Kidd and Ellis, 2012;EC, 2017;Kidd et al, 2019). While pollution from land is a dominant impact on marine ecosystems, marine pollution also derives from maritime activities (e.g., lost fishing gear and oil spills).…”
Section: Target 141 Marine Pollutionmentioning
confidence: 99%
“…Necesidad de gestión conjunta del medio marino y el costero. Tierra, costas y océanos deben ser manejados como una unidad integrada (Kidd et al, 2019) Necesidad de gestión conjunta del medio marino y el costero. Necesidad de articular el Ordenamiento Territorial (Ley N°18308) con la Ley N° 19772 que regula el ordenamiento territorial y desarrollo sostenible del espacio costero del Océano Atlántico y del Río de la Plata conjuntamente con la Planificación Espacial Marina.…”
Section: Límites En El Río De La Plataunclassified
“…El mar cubre más de dos tercios de la superficie de nuestro planeta y proporciona una amplia gama de servicios y bienes ecosistémicos de los cuales depende toda la vida en la Tierra (Kidd et al, 2019). La globalización, la gobernanza débil y la creciente industrialización de los mares están teniendo un impacto sustancial en la sostenibilidad de muchos tipos de recursos marinos, dando lugar a importantes desafíos para la conservación y gobernanza.…”
Section: Introductionunclassified